Pengaruh Moralitas Individu Dan Ketaatan Aturan Akuntansi Terhadap Kecenderungan Kecurangan Akuntansi Pada Pemerintah Kota Ambon - Adonia Anita Batkunde; Putri Maya Dewi (Politeknik Ganesha Medan, 2022)
This study aims to find empirical evidence regarding the effect of individual morality and obedience to accounting rules on the tendency of accounting fraud in the Ambon City Government. The sample used in this study amounted to 60 respondents spread across 12 Regional Apparatus Organizations (OPD). The sampling technique used is purposive sampling technique. The data used is primary data collected through questionnaires. The data obtained were then analyzed using SPSS. The results of this study prove that individual morality has no significant effect on the tendency of accounting fraud. This means that the tendency of accounting fraud is not influenced by individual morality, and there is no difference between individuals who have high levels of morality and low levels of morality in accounting fraud tendencies. Whether the system is good or not in the scope of government, the opportunity to tend to commit fraud depends on the individual or the individual morality of each employee. In other words, whether or not the morality of individual employees does not influence certain employees to commit fraud as long as the environment and opportunities are supportive to rationalize their actions. In addition, the existence of self-awareness from each employee is one form of how to prevent accounting fraud. Compliance with accounting rules has a significant negative effect on the tendency of accounting fraud. The results of this study indicate that the higher the company's compliance with accounting rules, the lower the tendency of accounting fraud by management to the company.